Nonconventional methods of injection molding - Bociąga, E. (Polimery, 2022)
Nonconventional methods of polymer injection molding allow to produce the parts showing properties and surface quality difficult or even impossible to obtain by the conventional injection molding process. These methods can be classified using different criteria, such as incorporation of additional materials or components into the molded part, melt formulation, melt manipulation, additional mold movement and special part or geometry features. Selected methods of nonconventional injection molding were described in the article. One of them is the microlayer injection molding, which enables to produce the parts consisting of a lot of very thin layers from at least two different polymers. Process of in-mold decoration is a combination of conventional injection molding and part printing. During in-mold lamination a multilayer laminate is positioned in a mold-parting plane and covered on one side by the injected polymer. Injection molding process can also be applied for metal-ceramic powders, mixed with thermoplastic and wax. By this method parts of good mechanical properties, complicated shape, made of almost unworkable materials, usually without additional machining can be manufactured. The push-pull process is characterized by the multiple polymer flow in cavity, in two directions, which causes significant macromolecule orientation in a core of parts and improves their mechanical properties in the flow direction. Multiple polymer flow in two directions lowers the possibility of weld lines appearance. During the rheomolding process a polymer melt, before its entering the mold or inside the mold, undergoes low frequency vibration to increase its rheological, mechanical and optic properties. Vibration reduces or even eliminates weld lines creation. Nonconventional methods of injection molding are performed using machines and equipment of more complicated constructions, their technologies are more difficult, but these methods allow to produce the products of specific properties required.